2003
DOI: 10.1038/sj.npp.1300204
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Epistasis Between the Serotonin Transporter and Norepinephrine Transporter Genes in Anorexia Nervosa

Abstract: Weight-restored patients with anorexia nervosa (AN) respond favorably to the selective serotonin reuptake inhibitor fluoxetine, which justifies association studies of the serotonin transporter gene (SLC6A4, alias SERT) and AN. Case-control studies suggest that the least transcriptionally active allele of the SERT gene promoter polymorphism (5-HTTLPR) has an increased frequency in AN patients. However, this finding was not replicated with 55 trios (AN child+parents) and the transmission disequilibrium test (TDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…The independent contribution by MAOA-L to increased risk of panic disorder is also thought to be small. 5 To date no one has attempted a replication study to confirm or refute our findings regarding MAOA-L. 9 Recently, we found no evidence for an independent contribution by the 5-HTTLPR to AN susceptibility in our family-based sample of at least a genotypic relative risk of 2.0 with 93% statistical power (odds ratio 1.0, 95% CI 0.7 -1.5), 10 which confirmed independent findings by others in three earlier studies. 11 -13 Data from the only other independent study of AN and the 5-HTTLPR suggested association of AN-BP with the 5-HTTLPR-S allele and 5-HTTLPR-S/S genotype (both P ¼ 0.02).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…The independent contribution by MAOA-L to increased risk of panic disorder is also thought to be small. 5 To date no one has attempted a replication study to confirm or refute our findings regarding MAOA-L. 9 Recently, we found no evidence for an independent contribution by the 5-HTTLPR to AN susceptibility in our family-based sample of at least a genotypic relative risk of 2.0 with 93% statistical power (odds ratio 1.0, 95% CI 0.7 -1.5), 10 which confirmed independent findings by others in three earlier studies. 11 -13 Data from the only other independent study of AN and the 5-HTTLPR suggested association of AN-BP with the 5-HTTLPR-S allele and 5-HTTLPR-S/S genotype (both P ¼ 0.02).…”
Section: Introductionmentioning
confidence: 61%
“…14 Additionally, we found no suggestion of interaction between the NETpPR polymorphism and the 5-HTTLPR, that is, neither 5-HTTLPR allele appeared to increase risk of AN when 5-HTTLPR allele transmissions from 5-HTTLPR-S/L heterozygous parents were stratified based on the NETpPR genotypes of their children with AN. 10 To date no one has attempted a replication study to confirm or refute our negative interaction findings between the NETpPR polymorphism and the 5-HTTLPR. 10 In the current study, to further investigate our hypothesis that proteins which clear NE and 5-HT from the synaptic cleft modify susceptibility to develop AN, we assess potential interaction between the MAOA-uVNTR and 5-HTTLPR in 114 nuclear families.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…29,30 Findings for other serotonin-related genes (i.e., 5-HT7, 5-HT 1Db , 5-HTT, TPH) have largely been negative. 24,26,28,[31][32][33][34][35][36][37][38] Studies of other candidate genes have been broad in scope covering genes involved in neurotransmitter systems (e.g., dopamine, opioids) as well as the regulation of feeding and energy expenditure (e.g., neuropeptide Y, leptin, agouti-related protein). Only one or two studies have examined each candidate gene.…”
Section: Association Studiesmentioning
confidence: 99%
“…Bergen et al (41) Association Yes SERT, NET Urwin et al (37) TDT and Association No OPRD1 Bergen et al (41) Association Yes ER a Eastwood et al (48) Association No…”
Section: Htr1dmentioning
confidence: 99%